144 Recovery of the gastrointestinal tract in response to nutritional challenges. (7th December 2018) - Penner, G
Abstract: The gastrointestinal tract must respond appropriately to challenges while facilitating essential functions. Previous studies have focused on evaluating the impact of nutritional challenges such as dietary change, ruminal acidosis, or transient low feed intake. While the impact of the challenge is important, understanding the recovery of the gastrointestinal tract following a challenge has largely been overlooked. In response to 5-d of low feed intake, the recovery for dry matter intake and short-chain fatty acid absorption across the reticulo-rumen is delayed as the magnitude of low feed intake increased. Exposure to severe feed restriction also decreases barrier function of the gastrointestinal tract for at least 21 d. Moreover, the diet fed prior to low feed intake and following low feed intake can affect the severity of the induced response and the subsequent rate of recovery with more severe exposure delaying the response. However, for most instances, low feed intake is not predictable or the exact timeline for exposure cannot be accurately predicted. An unexpected outcome following low feed intake and upon return to ad libitum intake is the induction of ruminal acidosis: another challenge that the gastrointestinal tract must face and recover from. Recent studies have reported that in addition to low ruminal pH, induction of ruminal acidosis reduces pH in the large intestine and may compromise barrier function. However, the regions most affected remain unknown and may be affected by a rapid recovery response. In fact, the expression of genes related to tight-cell junctions were greater for cattle exposed to ruminal acidosis than for cattle not challenged. This may help explain why cattle adapted to a highly fermentable diet recover from ruminal acidosis more rapidly than cattle not adapted. A complete understanding regulatory factors that help accelerate recovery of the gastrointestinal tract following a challenge warrants further research.